Peningkatan Target Produksi Pengupasan Tanah Penutup Pada Penambangan Bijih Nikel CV. Sentosa Abadi Desa Bahomakmur, Kecamatan Bahodopi, Kabupaten Morowali, Provinsi Sulawesi Tengah - Alhabsyi, Gina Audina P; Idhan, Muh Arif; Bunga, Ruth; Sani, Hendra (Journal of Applied Geoscience and Engineering, 2023)
Nickel is the fifth most common chemical element on Earth. Several regions in Indonesia with large nickel content are East Luwu, South Sulawesi, Kolaka, Southeast Sulawesi, Morowali, Central Sulawesi, East Halmahera, North Maluku. Most nickel mines use a mining method with an open mining system (Surface Mining) using a method (Open Cut Mining), namely cutting from the ridge downwards. The mining stages are carried out by clearing land, stripping overburden, dredging ore, loading and hauling for purification and processing. CV. Sentosa Abadi is a Mining Contractor based in Palu City, Central Sulawesi and also has a site camp in Bahomakmur Village, Bahodopi District. The company uses an open cut process along with open-pit mining technology. Land clearing, removal of top soil and cover soil. The aim of this research is to determine the overburden production target in July at CV. Sentosa Abadi and to evaluate production increases which are influenced by waiting times. Calculating production targets is one way to plan and control production, apart from that, production targets can also be defined as a tool to carry out effective and efficient planning. From research This is the volume of overburden produced during one month with total production of 296,927.7 bcm.